Chronic Stress Oppositely Regulates Tonic Inhibition in Thy1-Expressing and Non-expressing Neurons in Amygdala - Pan, Han-Qing; Zhang, Wen-Hua; Liao, Cai-Zhi; He, Ye; Xiao, Zhi-Ming; Qin, Xia; Liu, Wei-Zhu; Wang, Na; Zou, Jia-Xin; Liu, Xiao-Xuan; Pan, Bing-Xing (Frontiers in Neuroscience, 2020)
Chronic or prolonged exposure to stress ranks among the most important socio-environmental factors contributing to the development of neuropsychiatric diseases, a process generally associated with loss of inhibitory tone in amygdala. Recent studies have identified distinct neuronal circuits within the basolateral amygdala (BLA) engaged in different emotional processes. However, the potential circuit involved in stress-induced dysregulation of inhibitory tones in BLA remains elusive. Here, a transgenic mouse model expressing yellow fluorescent protein (YFP) under control of the Thy1 promoter was used to differentiate subpopulations of projection neurons (PNs) within the BLA. We observed that the tonic inhibition in amygdala neurons expressing and not expressing Thy1 (Thy1+/-) was oppositely regulated by chronic social defeat stress (CSDS). In unstressed control mice, the tonic inhibitory currents were significantly stronger in Thy1- PNs than their Thy1+ counterparts. CSDS markedly reduced the currents in Thy1- projection neurons (PNs), but increased that in Thy1+ ones. By contrast, CSDS failed to affect both the phasic GABAAR currents and GABABR currents in these two PN populations. Moreover, chronic corticosterone administration was sufficient to mimic the effect of CSDS on the tonic inhibition of Thy1+ and Thy1- PNs. As a consequence, the suppression of tonic GABAAR currents on the excitability of Thy1- PNs was weakened by CSDS, but enhanced in Thy1+ PNs. The differential regulation of chronic stress on the tonic inhibition in Thy1+ and Thy1- neurons may orchestrate cell-specific adaptation of amygdala neurons to chronic stress.